1977
DOI: 10.1051/rphysap:019770012070100700
|View full text |Cite
|
Sign up to set email alerts
|

Distribution radiale des atomes excités dans une colonne positive de néon

Abstract: La distribution radiale des atomes de néon excités dans les états 2p 5 3p et 2p5 3s est expérimentalement déterminée dans la colonne positive d'une décharge continue. Le couplage électronique entre ces configurations est étudié pour des pressions variant entre 0,5 et 4 torrs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…For these calculations we used an average electron speed of 8.8 × 10 7 cm s −1 corresponding to a temperature of 3.0 eV measured with a single Langmuir probe [46] for the electrons in the bulk of the energy distribution. This temperature agrees well with the value of 2.8 eV measured by Valignat et al [48] in the positive column of a similar neon discharge. Again there is good agreement between these and our fitted values.…”
Section: Electron Collisional 1s-2p Rate Coefficientssupporting
confidence: 92%
See 1 more Smart Citation
“…For these calculations we used an average electron speed of 8.8 × 10 7 cm s −1 corresponding to a temperature of 3.0 eV measured with a single Langmuir probe [46] for the electrons in the bulk of the energy distribution. This temperature agrees well with the value of 2.8 eV measured by Valignat et al [48] in the positive column of a similar neon discharge. Again there is good agreement between these and our fitted values.…”
Section: Electron Collisional 1s-2p Rate Coefficientssupporting
confidence: 92%
“…Table 3. Fitted and values from the literature of the excitation rate coefficients, S ij , for all of the allowed 1s-2p transitions at 2 Torr, expressed in units of 10 −7 cm 3 s −1 , where (a) are obtained from our LCIF fitting, (b) are the corresponding rate coefficients found by using a temperature of 3.0 eV, as measured by single Langmuir probe [46], and the modified average cross section approximation of Hyman [28] together with the oscillator strengths given by Taylor et al [44], and (c) found by combining the average electron speed for this temperature with the data presented by Valignat et al [48] for the Drawin cross section formula [27]. The 1s 2 -2p excitation coefficients have been omitted since the 1s 2 level plays a very minor role in the LCIF.…”
Section: Electron Collisional 1s-2p Rate Coefficientsmentioning
confidence: 97%